2009
DOI: 10.1089/neu.2008.0857
|View full text |Cite
|
Sign up to set email alerts
|

Early Mitochondrial Dysfunction after Cortical Contusion Injury

Abstract: Following traumatic brain injury, mitochondria sustain structural and functional impairment, which contributes to secondary damage that can continue for days after the initial injury. The present study investigated mitochondrial bioenergetic changes in the rat neocortex at 1 and 3 h after mild, moderate, and severe injuries. Brains from young adult Sprague-Dawley rats were harvested from the injured and contralateral cortex to assess possible changes in mitochondrial respiration abilities following a unilatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 47 publications
2
52
0
Order By: Relevance
“…Cyclosporin A, a calcineurin inhibitor, has shown good neuroprotective effect in preclinical animal studies of TBI (89)(90)(91), presumably by inhibiting the Ca 2+ -induced mitochondrial membrane permeability transition leading to less mitochondrial swelling and rupture of the outer mitochondrial membrane (92). In a randomized controlled trial treating severe TBI patients with cyclosporin A, monitored with MD, brain energy metabolism improved significantly in the treated group (25).…”
Section: Pharmacokinetics Of Neuroprotective Agentsmentioning
confidence: 99%
“…Cyclosporin A, a calcineurin inhibitor, has shown good neuroprotective effect in preclinical animal studies of TBI (89)(90)(91), presumably by inhibiting the Ca 2+ -induced mitochondrial membrane permeability transition leading to less mitochondrial swelling and rupture of the outer mitochondrial membrane (92). In a randomized controlled trial treating severe TBI patients with cyclosporin A, monitored with MD, brain energy metabolism improved significantly in the treated group (25).…”
Section: Pharmacokinetics Of Neuroprotective Agentsmentioning
confidence: 99%
“…The majority of the previous animal studies of mitochondrial function in TBI have shown that mitochondrial damage occurs rapidly as early as 1 h postinjury (3,4), with peak mitochondrial respiratory chain dysfunction at 12-24 h (5). However, the effects of TBI on mitochondrial function at later stages of secondary brain damage remain unclear.…”
Section: Tbimentioning
confidence: 99%
“…TBI precipitates a complex, secondary pathophysiological process which can result in a cascade of deleterious side effects often far from the site of the initial injury, and which places tissue that survives the initial insult at risk for functional failure, neurodegeneration, apoptosis, and death (Hattori et al, 2003; Marcoux et al, 2008b; Ragan et al, 2013; Xu et al, 2010). A growing body of literature suggests that a main component of this secondary injury cascade is altered mitochondrial bioenergetics and cerebral metabolic crisis (Gilmer et al, 2009; Robertson et al, 2006). Mitochondria play a pivotal role in cerebral metabolism and regulation of oxidative stress, excitotoxicity, and apoptosis (Balan et al, 2013; Gilmer et al, 2009; Lifshitz et al, 2003; Robertson, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of literature suggests that a main component of this secondary injury cascade is altered mitochondrial bioenergetics and cerebral metabolic crisis (Gilmer et al, 2009; Robertson et al, 2006). Mitochondria play a pivotal role in cerebral metabolism and regulation of oxidative stress, excitotoxicity, and apoptosis (Balan et al, 2013; Gilmer et al, 2009; Lifshitz et al, 2003; Robertson, 2004). Cerebral metabolic crisis displays regional heterogeneity, varies temporally post-injury and with gradation of injury severity, and is often sustained for a prolonged period of time (Lifshitz et al, 2003; Marcoux et al, 2008b; Ragan et al, 2013; Robertson et al, 2006, 2009; Saito et al, 2005).…”
Section: Introductionmentioning
confidence: 99%